Current Advances in Osteosarcoma - Kleinerman, M.D., Eugenie S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Current Advances in Osteosarcoma summarizes molecular and genetic characteristics, new therapeutic ideas, and biological characteristics that have been uncovered in this field over the past 10 years. Osteosarcoma is an aggressive malignant neoplasm and is the most common histological form of bone cancer. Osteosarcoma accounts for approximately 56% of new bone tumors, making it the most primary malignant bone tumor in children and adolescents. The lungs are the most common site of metastases and once osteosarcoma spreads to the lungs, it is very difficult to treat. In order to improve the outcome of this disease, the biology of osteosarcoma needs to be better understood. There are numerous investigators around the world who have made seminal discoveries about the important molecular pathways and genetic alterations that contribute to the development and metastases of osteosarcoma. Other investigators have proposed novel therapeutic strategies including some based on the molecular and genetic phenotype of the disease. This volume will provide a comprehensive review of these new discoveries in one singular text, which will help move the field forward.
Historical Perspective on the Introduction and Use of Chemotherapy for the Treatment of Osteosarcoma -- Wnt Signaling in Osteosarcoma -- Receptor Tyrosine Kinases in Osteosarcoma: Not Just the Usual Suspects -- Understanding the Role of Notch in Osteosarcoma -- Developmental Pathways Highjacked by Osteosarcoma -- MicroRNAs in Osteosarcomagenesis -- RECQ DNA Helicases and Osteosarcoma -- Autophagy in Osteosarcoma -- HER-2 Involvement in Osteosarcoma -- Role of Ezrin in Osteosarcoma Metastasis -- Participation of the Fas/FasL Signaling Pathway and the Lung Microenvironment in the Development of Osteosarcoma Lung Metastases -- Zebrafish as a Model for Human Osteosarcoma -- Using Canine Osteosarcoma as a Model to Assess Efficacy of Novel Therapies: Can Old Dogs Teach Us New Tricks? -- Oncolytic Viruses for Potential Osteosarcoma Therapy -- IL-11Rα: A Novel Target for the Treatment of Osteosarcoma -- Bone-seeking Radiopharmaceuticals as Targeted Agents of Osteosarcoma: Samarium-153-EDTMP and Radium-223 -- Muramyl Tripeptide-phophatidyl Ethanolamine Encapsulated in Lipomes (L-MTP-PE) in the Treatment of Osteosarcoma -- Genetically Modified T-cell Therapy for Osteosarcoma -- Natural Killer Cells for Osteosarcoma.
Keywords: Cancer research; Medical microbiology; Cell biology; Pediatrics; Cancer Research; Medical Microbiology; Cell Biology; Pediatrics